Big Challenge. - Hoffmann, Leah (Communications of the ACM, 2013)
An interview with Jeff Dean and Sanjay Ghemawat of Internet company Google and recipients of the 2014 ACM-Infosys Foundation Award in the Computing Sciences, is presented. They describe their initial collaboration on a project at Digital Equipment Corp. They discuss their work and the office they both share at Google. They discuss the issue on scalability in one of their projects called MapReduce, which helps computer programmers to spread their computations across multiple machines.